1261Geographical variations in the incidence of CIED infection and infection prevention strategies: Update from the global WRAP-IT study. (18th June 2020) - Kennergren, C; Poole, J E; Wilkoff, B L; Mittal, S; Corey, G R; Mccomb, J; Diemberger, I; Wright, D J; Philbert, B T; Simmers, T A; Boersma, L V A; Debus, B; et al.
Abstract: Funding Acknowledgements: Medtronic, Inc. Introduction: Cardiac Implantable Electronic Device (CIED) infections lead to significant morbidity, mortality, and use of health care resources. There is variation in infection prevention strategies among centers, and it is not clear whether there is also variation in infection rates across different geographies. Recently, WRAP-IT, the largest global randomized trial to evaluate an infection reduction strategy, randomized 6, 983 patients to receive an antibacterial envelope (treatment) vs. no envelope (control). The results demonstrated a significant reduction in major CIED infection with the TYRX antibiotic envelope (12-mo infection rate for envelope vs. control 0.7% and 1.2%, respectively; HR, 0.60; 95% [CI], 0.36 to 0.98; P = 0.04).  The purpose of this analysis is to assess geographical variations in patient characteristics, procedural routines, and infection rates. Methods: The WRAP-IT study enrolled patients undergoing a CIED pocket revision, generator replacement, or system upgrade or an initial implantation of a cardiac resynchronization therapy defibrillator and randomized them to receive the envelope or not, in addition to mandated pre-procedure intravenous antibiotic prophylaxis. To assess geographical variations in infection rates, the control group (per protocol) baseline demographics and procedural characteristics were identified. Major infection was defined as CIED infections resulting in system extraction or revision, long-term antibiotic therapy with infection recurrence, or death. Results: A total of 3429 control patients were evaluated and followed for a mean of 20.9 ± 8.3 months; 2530 patients from 123 centers in North America, 777 patients from 46 centers in Europe, and 122 patients from 11 centers in Asia/South America. The 24-month Kaplan-Meier major infection rates were 1.2% in North America (30 pts), 2.5% in Europe (16 pts), and 4.3% Asia/South America (5 pts) (see Figure). These geographical variations in the incidence of major CIED infections were significant (overall P = 0.008, univariate). There were differences in baseline patient characteristics, including age, sex, medication use, NYHA Class, and number of previous devices across geographies. Differences also included procedural characteristics, such as device type, use of pocket wash, skin preparation, pre-operative antibiotic drug use, and procedure time. Conclusion: Major CIED infection rates vary significantly across geographies. The effect of patient demographics and procedural characteristics on these findings will be assessed and presented at EHRA. Insights into geographical variability of CIED infections is important to mitigate infection risk, reduce morbidity and cost.